Hofbauer Cells: Their Role in Healthy and Complicated Pregnancy - Reyes, Leticia; Golos, Thaddeus G. (Frontiers in Immunology, 2018)
Hofbauer cells are placental villous macrophages of fetal origin that are present throughout pregnancy. Although Hofbauer cell populations are antigenically and morphologically heterogeneous, their epigenetic, antigenic, and functional profiles most closely resemble alternatively activated macrophages or what are referred to as M2a, M2b, M2c, and M2d polarity subtypes. Consistent with an M2-like profile, these cells play an important role in placental development including vasculogenesis and angiogenesis. During placental inflammation Hofbauer cells may produce pro-inflammatory cytokines or mediators that damage the villous cell barrier, and induce fibrotic responses within the villi as a continuum of chronic inflammation. However, to date, there is no evidence that Hofbauer cells become classically activated or adopt an M1 polarity phenotype that is able to kill microbes. To the contrary, their predominant M2 like qualities may be why these cells are ineffective in controlling most TORCH infections. Moreover, Hofbauer cells may contribute to vertical transmission of various pathogens to the fetus since they can harbor live virus and serve as reservoirs within the placenta. The goal of this review is to summarize what is currently known about the role of Hofbauer cells in normal and complicated pregnancies that involve immunologic disorders, inflammation, and/ or infection.